EVALUATION OF DIABETIC FOOT COMPLICATIONS IN OPD PATIENTS AT DIFFERENT HOSPITALS OF DISTRICT NAUSHAHRO FEROZE (The Research of Medical Science Review, 2025)
Diabetic foot is a global epidemic of 21th century and it is a major health problem. Foot complications in patients with Diabetes mellitus (DM) are a major health problem and account for 20% annual Diabetes related hospital admissions. This study was made in order to evaluate Diabetic foot complications in outdoor patients (OPD) at different hospitals from district Naushahro Feroze Sindh. This cross-sectional descriptive study was carried out from June to November 2021. It aims to find out the prevalence and causes of foot complications in type I and type II Diabetes mellitus patients and to find out the commonest complication in the area. The data was collected from the predesigned proforma and frequency, percentage, mean were analyzed and calculated statistically. During research period total 74 patients of type I and type II Diabetes mellitus patients were evaluated for Diabetic foot complications. Male to female ratio was 1.3:1. The ratio of type I and type II DM was 1:6.4. The commonest age group of patients was between 31- 45 years. 44 (59.4%) patients were educated (hardly five to seven or eight class). (40.54%) patients were uneducated. In our study most common foot complication was foot ulcer/ wound infection (33.7%). Second most common complication was diabetic foot gangrene (27.03%). Other foot complications were peripheral neuropathy (24.32%), foot abscess (10.81%) and cellulitus (4.05%). 35 patients (47.2%) cames with history of hereditary (genetics) and 39 (52.7%) patients had history of acquired disease. People educated/uneducated in District Naushahro feroze are unaware of DM and its complications Therefore public (patients) awareness about DM, foot complications and foot care is strongly needed in District Naushahro feroze Sindh.